Strategic Planning in Increasing Quality of Education - Pebriana Priyambodo; Enung Hasanah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
This research is motivated by the low quality of education in Indonesia, especially primary education. Improving the quality of education is a must to meet the needs of schools and communities. One of the efforts made to make schools an active forum in improving the quality of education is strategic planning. This study aims to explore school strategic planning, analyze, and plan strategic planning in improving the quality of education at SDN Jetis Bantul. Researchers used descriptive research with a qualitative approach. Data collection techniques in this study were in-depth interviews, participant observation and documentation. This study's subjects were the principal, members of the principal's work deliberation, supervisors, teachers, and the school committee. Data analysis techniques used are data, data reduction, data presentation, drawing conclusions and levers. The results show that: (1) strategic planning is carried out by making an annual work plan following the vision, mission and goals of the school formulated at the beginning of the school year, forming a school development team, implementing school planning by educational procedures, developing development and coaching results achieving goals. (2) implementing school management strategies to diagnose systematically, plan, design and compile documents, establish policies, motivate educators and education personnel, allocate human resources, and develop a supportive strategic culture. (3) The evaluation of the school management strategy is carried out by analyzing its suitability with the strategic plan; the evaluation results used to assess a program, improvements, or colours. Supporting strategic planning factors are excellent support from students, teachers, supervisors, committees, student guardians and the school environment. The obstacle encountered in school strategic planning is the problem of the improper formulation. The school collaborates with the school committee and student guardians to solve these inhibiting factors to overcome this.